ANALYSIS OF MICROORGANISMS COMMUNITIES PROFILE IN TAUCO FERMENTATION WITH CULTURE-DEPENDENT APPROACH - Yanuar Pauzi, Rizqi
Tauco is a typical Indonesian soybean fermented food. Many people who eat this food because in addition to have a distinctive taste also has good potential for health. The process of making tauco is still traditional without the standardization of the process and the addition of strater culture so that it influences the consistency of the quality of the tauco product. Tauco fermentation lasts for 106 days which consists of several stages namely mold fermentation, brine fermentation and aging stage. The purpose of this study is to determine the dynamics of microbial communities during the tauco fermentation process with a cultivation approach. The methods carried out in this study were isolation, enumeration, morphological identification, analysis of 16S rRNA for bacteria and ITS for fungi, phylogenetic analysis, diversity analysis and Principal Component Analysis (PCA). The results of isolation during tauco fermentation found 7 fungal isolates and 9 bacterial isolates. During fermentation of molds, the fungi obtained were Aspergillus oryzae, Aspergillus ochraceus, and Lictheimia ramosa. These fungi play a role in degrading soybean macromolecular compounds into smaller compounds. Pichia kudriazevi and Millerozyma farinosa are yeasts found during salt fermentation. Whereas in further fermentation only one yeast is dominated by Candida etchelsii. The results of bacterial isolation showed that Pseudomonas sp. and Bacillus subtilis DSM 10 strain is found in mold fermentation. Salt fermentation is dominated by Enterococcus faecium while in advanced fermentation it is dominated by Bacillus genus such as Bacillus subtilis SBMP4 strain, Bacillus subtilis H4 strain and Bacillus licheniformis. As for the sweet tauco product, Stenotrophomonas pavani was found. The results of the mushroom diversity analysis showed that the highest diversity index was obtained at the beginning of mold fermentation with a value of 1.19 with the criteria being medium. While the analysis of bacterial diversity showed that the highest diversity index was obtained at the beginning of further fermentation with a value of 1.44. The results of enzymatic abilities indicate that the filament fungi and bacteria of the Bacillus genus show the ability to degrade macromolecular compounds. While yeast shows the ability to degrade simple molecules. Therefore, from the results of this study can be selected key microorganisms that can be used in tauco fermentation namely Aspergillus oryzae, Candida etchelsii, and Bacillus subtilis.